Contribution to the assessment of the genetic potential of wild pear mother trees from the landscape of outstanding features ”Kosmaj” - Nonić Marina; Inđić Anđela; Kerkez-Janković Ivona; Maksimović Filip; Devetaković Jovana; Šijačić-Nikolić Mirjana (Glasnik Šumarskog Fakulteta: Univerzitet u Beogradu)
Native species of forest fruit trees represent an important component of biodiversity, but are often threatened by the effects of various biotic and abiotic factors. In the Landscape of outstanding features “Kosmaj”, the following forest fruit trees were recorded: wild cherry, wild pear, wild service tree and service tree, which are among the endangered or vulnerable species in this area. In order to assess the genetic potential of wild pear mother trees from the Kosmaj area, a generative progeny test was established in the nursery of the Faculty of Forestry. The variability of morphological characteristics of one-year-old seedlings from 14 half-sib lines was analyzed, the survival of seedlings was recorded, and their height and root collar diameter were measured. The mother trees DK4, DK22 and DK23 stood out as potentially superior due to the percentage of survival and the high values for height and root collar diameter of the seedlings of the half-sib lines. The genetic potential of these mother trees and their half-sib lines should be tested in the coming years, with regard to resistance to biotic and abiotic factors, in nursery progeny test and field trials.